LPL protein in Chronic Lymphocytic Leukaemia have different origins in Mutated and Unmutated patients. Advances for a new prognostic marker in CLL. (28th June 2018) - Prieto, Daniel; Seija, Noé; Uriepero, Angimar; Souto‐Padron, Thais; Oliver, Carolina; Irigoin, Victoria; Guillermo, Cecilia; Navarrete, Marcelo A.; Inés Landoni, Ana; Dighiero, Guillermo; Gabus, Raúl; Giordano, Mirta; et al.
Summary: Lipoprotein lipase ( LPL ) mRNA expression in chronic lymphocytic leukaemia (CLL) is associated with an unmutated immunoglobulin profile and poor clinical outcome. We evaluated the subcellular localization of LPL protein in CLL cells that did or did not express LPL mRNA. Our results show that LPL protein is differently located in CLL cells depending on whether it is incorporated from the extracellular medium in mutated CLL or generated de novo by leukaemic cells of unmutated patients. The specific quantification of endogenous LPL protein correlates with mRNA expression levels and mutational IGHV status, suggesting LPL protein as a possible reliable prognostic marker in CLL.